A comparative analysis of the efficacy of intrauterine misoprostol in conjunction with oxytocin versus oxytocin monotherapy for the prophylaxis of primary postpartum haemorrhage - Afnan Rizwan; Farooq, Muhammad Hassaan; Uzma Nayyer; Asma Irfan; Mahwish Farooq; Maryam Siddique (Journal of the Pakistan Medical Association, 2025)
Objectives: To determine the effectiveness of intrauterine misoprostol along with oxytocin versus oxytocin monotherapy for the prevention of primary postpartum haemorrhage. Method: The quasi-randomised controlled trial took place at the Akbar Niazi Teaching Hospital, Islamabad, Pakistan, from February to August 2021, and comprised women who underwent lower segment caesarean section and at full-term pregnancy who had risk factors for experiencing postpartum haemorrhage. The subjects were randomised into experimental group A and control group B. Group A subjects received both misoprostol and oxytocin, while those in group B received oxytocin only. Data was analysed using SPSS 26. Results: Of the 120 subjects, 60(50%) were in group A with mean age 28.72±5.82 years and mean gestational age 38.02±1.1 weeks. The remaining 60(50%) subjects were in group B with mean age 29.47±4.72 years and mean gestational age 37.50±1.5 weeks. Group A subjects had fewer changes in haemoglobin levels post-operation than those in group B (p<0.05). The number of operative towels used, contractility time of the uterus, and need for other drugs to control haemorrhage were significantly different in group A compared to group B. Conclusion: Misoprostol along with oxytocin was found to be more effective in reducing blood loss in patients with postpartum haemorrhage. Key Words: Postpartum haemorrhage, Misoprostol, Oxytocin, Postoperative blood loss.